Hindered Urea Bond: A Bilaterally Responsive Chemistry to Hydrogen Peroxide. Issue 4 (15th January 2019) - Ying, Hanze; Yang, Yingfeng; Cai, Kaimin; Cheng, Jianjun
Abstract : As a type of safe, clean, and bio‐relevant oxidant, hydrogen peroxide has been widely used as a trigger in the design of stimuli‐responsive materials. Hindered urea bond (HUB) is a type of dynamic covalent bond which can reversibly dissociate into isocyanate and amine. Quenching of isocyanate or amine will shift the equilibrium and facilitate the degradation of HUB bond. Herein, we report that one of the HUB moiety – 1, 1‐ tert ‐butylethylurea (TBEU) can react with hydrogen peroxide (H2 O2 ) resulting in two opposing outcomes. Perhydrolysis of isocyanate and oxidation of amine lead to the bond fracture, while formation of urethane product with an oxygen inserted into the original TBEU structure was also observed giving a stabilized form of linkage. More precise kinetic control of the two distinct pathways are expected to make hydrogen peroxide a trigger to either degrade or fix the HUB based polymeric materials. Abstract : The hindered urea bond, a type of dynamic covalent bond which can reversibly dissociate into isocyanate and amine, responds to hydrogen peroxide in two opposing ways: Perhydrolysis of isocyanate and oxidation of amine lead to the bond fracture; while formation of a urethane product with an oxygen inserted into the original urea structure gives a stabilized form of linkage.